Collective Labor Agreements (CLA) in Foreign Capital Companies: Gustav Radbruch's Perspective - Yeltriana, Yeltriana; Batubara, Ismed; Saragih, Alkausar (JURNAL AKTA, 2025)
Analysis of Collective Labor Agreements in ultinational corporation through the lens of Gustav Radbruch's theory underlines the importance of material justice, legal certainty, and the conformity between legality and morality in industrial relations. Radbruch's theory provides a comprehensive framework for evaluating the fairness and effectiveness of Collective labor Agreements, emphasizing the important role of trade unions in protecting workers' rights and ensuring fair implementation of Collective labor Agrements. The application of Radbruch's principles in this context requires active cooperation from all stakeholders, including the government, employers, and trade unions. The government has the responsibility to create a legal environment that supports justice and legal certainty, while employers must respect workers' rights and comply with the contents of Collective labor Agreements. Trade unions, as representatives of workers, have a crucial role in ensuring that workers' voices and interests are heard and considered in the process of negotiating and implementing Collective labor Agreements